Topic Subjects in Brazilian Portuguese and Clitic Left Dislocation in Dominican Spanish: The Role of Clitics and Null Subjects. (14th July 2019) - Kato, Mary A.; Ordóñez, Francisco
Abstract: Brazilian Portuguese used to have null subjects like European Portuguese, but today they are mostly lost. It has been claimed that this change to the null‐subject parameter made Brazilian Portuguese no longer a subject‐prominent language (aka an agreement‐prominent language) but a topic‐and‐subject‐prominent one, with the appearance of so‐called topic subjects. In this article, we show that the loss of null subjects in Brazilian Portuguese is not sufficient to explain the emergence of topic subjects: the generalized loss of third‐person clitics also plays a crucial role. We provide evidence from within Brazilian Portuguese, comparing topic‐subject constructions to clitic‐left‐dislocation constructions with first‐ and second‐person pronouns; we also compare Brazilian Portuguese to Dominican Spanish, a language that has also mostly lost null subjects but has retained its entire clitic system. We show that what is behind the appearance of topic‐subject constructions in Brazilian Portuguese is the partial disappearance of clitic left dislocation, a topic construction that Dominican Spanish has retained for all persons. The analysis proposed appeals to empty dative clitics and their inability to assign case in Brazilian Portuguese. Finally, we adopt the feature‐inheritance hypothesis (Miyagawa 2010) in order to derive the topicality of Brazilian Portuguese's so‐called topic subjects.